Needs Analysis for Designing Hybrid Learning with Problem-Based Scaffolding to Enhance Mathematical Problem-Solving Skills - Yani Setiani; Yayat Ruhiat; Aan Hendrayana (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study aimed to identify the need for developing a hybrid learning design integrated with problem-based scaffolding to improve students' mathematical problem-solving skills in a differential equations course. A quantitative approach was employed, involving surveys and in-depth interviews with 104 mathematics education students at Sultan Ageng Tirtayasa University. The results showed that 88% of students valued the flexibility of hybrid learning, while 85% agreed that problem-based learning effectively supported their ability to solve complex problems. Additionally, 83% found step-by-step scaffolding helpful, and 88% emphasized the importance of timely feedback. These findings highlight the critical need for structured scaffolding tailored to student abilities, supported by multimedia instructional tools such as videos combining PowerPoint and screencast recordings. The study recommends integrating these components into mathematics instruction and regular formative assessments to enhance student engagement and problem-solving competence. The results provide practical guidance for curriculum designers and educators seeking to implement more effective and relevant learning models in higher education mathematics.